Hipochondria (lęk o zdrowie): obecna konceptualizacja, klasyfikacja oraz podobieństwo do zaburzeń lękowych = Hypochondriasis (health anxiety): current conceptualization, classification and overlap with anxiety disorders - Janusz Kocjan (Kazimierz Wielki University, 2015)
Kocjan Janusz. Hipochondria (lęk o zdrowie): obecna konceptualizacja, klasyfikacja oraz podobieństwo do zaburzeń lękowych = Hypochondriasis (health anxiety): current conceptualization, classification and overlap with anxiety disorders. Journal of Education, Health and Sport. 2015;5(5):193-204. ISSN 2391-8306. DOI 10.5281/zenodo.17582 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A193-204 https://pbn.nauka.gov.pl/works/559804 http://dx.doi.org/10.5281/zenodo.17582 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   HIPOCHONDRIA (LĘK O ZDROWIE): OBECNA KONCEPTUALIZACJA, KLASYFIKACJA ORAZ PODOBIEŃSTWO DO ZABURZEŃ LĘKOWYCH Hypochondriasis (health anxiety): current conceptualization, classification and overlap with anxiety disorders   Janusz Kocjan   Wydział Lekarski, Śląski Uniwersytet Medyczny, Katowice, Polska Faculty of Medicine, Medical University of Silesia, Katowice, Poland   STRESZCZENIE Klasyfikacja i rozpoznanie hipochondrii od zawsze stanowiło poważny problem oraz budziło wiele wątpliwości. W ostatnich latach związaną z tym problematykę określono w literaturze mianem jednego z najbardziej kontrowersyjnych i trudnych obszarów nowoczesnej psychiatrii. W świetle dotychczasowych podziałów taksonomicznych, hipochondria przez długi czas klasyfikowana była jako zaburzenie somatyczne. Koncepcyjnie jednak, najlepiej rozumiana jest jako zaburzenie lękowe (lęk o zdrowie). Kilka teoretycznych modeli stara się wyjaśnić przyczyny występowania oraz utrzymywania ciężkiego lęku o zdrowie (kliniczna forma hipochondrii), m.in. model poznawczo-behawioralny oraz model interpersonalny. Słowa kluczowe: hipochondria, lęk o zdrowie, DSM-V, ICD-10.   SUMMARY Classification and diagnosis of hypochondria has always been a serious problem and raised a many doubts. In literature, this problem have been described recently as one of the most difficult and challenging areas of modern psychiatry. In the light of previous taxonometric studies, hypochondria was classified as a somatoform disorders for a long time. However, conceptually is best understood as an anxiety disorder (health anxiety). Several theoretical model endavour to explain the development and maintenance of severe health anxiety (clinical form of hypochondriasis), including  cognitive-behavioral model and interpersonal model. Key words: hypochondriasis, health anxiety, DSM-V, ICD-10.